Extension of Digital Media to Strengthen Learning Outcome with Online Approach in Inclusive School Students - Abdul Basit; Renny Candradewi Puspitarini (Journal of Development Research, 2019)
This study aims to strengthen the learning outcomes of civic teachers by providing excellent service not only in learning process but also external activities beyond classrooms at inclusive schools. Research informants involved are inclusive students (with special needs), regular students, civic teachers, and school principals. The research approach is qualitative research of analytical descriptive. The process of collecting data encompasses process of observation, interviews, and documentation studies. The results indicate success in the learning process by significantly increasing the inclusive students' learning abilities. The activities of inclusive students were also better than before with their involvement in the I-Spring Suite-based education and training activities by all teachers.